Enhancing Quranic Education For Autistic Children in Malaysia: A Systematic Literature Review - Yuslina Mohamed; Wan Azura Wan Ahmad; Sulaiman Ismail; Mesbahul Hoque; Nada Ibrahim Alribdi (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia